Implementasi Program Jaminan Sosial Ketenagakerjaan Pada Pekerja Formal Di BPJS Ketenagakerjaan Tanjung Perak: Program Jaminan Sosial Ketenagakerjaan - Wulan Nur Fath-Hiah; Binti Azizatun Nafi’ah (Public Inspiration : Jurnal Administrasi Publik, 2023)
Employment social security is a program of the Government of Indonesia organized by the Employment Social Security Administration Agency (BPJS) with the aim of protecting all workers in Indonesia. To make the program policy successful, socialization activities need to be carried out. This research focuses on formal workers or wage workers (PU) in the city of Surabaya. In government regulations, companies that have an NIB are required to register business entities and their employees in the BPJS Ketenagakerjaan program. This study aims to describe and find out the implementation of the employment social security program for formal workers at BPJS Ketenagakerjaan by using the policy implementation theory according to Merilee S. Grindle. The research method used by the author is descriptive qualitative research. Based on the results obtained, the implementation of the employment social security program for formal workers at the Tanjung Perak Employment BPJS is not optimal. This is because there are still many business entities that have not registered their companies and employees in the BPJS Employment program. This is evidenced by the internal data of the Tanjung Perak Employment BPJS, which recorded that only 8.28% of companies out of 1,130 company acquisitions in the Surabaya area were participants of the Employment BPJS.